Effect of perceived teaching quality on the perceived co-determination of primary school children - Leonora Gerbeshi (Cogent Education)
Children’s co-determination in school is particularly important from the perspective of children’s rights and democratic education. Current research indicates that children generally perceive limited co-determination in the classroom context, primarily regarding organisational rather than teaching aspects. The role of teaching quality in this context remains unclear. This article presents the results of a cross-sectional questionnaire study (N = 472 third-graders from 28 classes), using multilevel modelling to examine the effect of perceived supportive climate and classroom management on perceived co-determination in the classroom (Level 2) while considering other predictors such as gender, migration history, self-determination, desire for co-determination (Level 1) and class size (Level 2). The results of the multilevel analyses reveal that a supportive climate is particularly significant for perceived co-determination regarding organisational aspects but not for teaching aspects. Apart from the opportunities for discussion and exchange in terms of organisational aspects, classroom management was found not to be statistically significant for perceived co-determination. Regarding the other variables, the perceived self-determination significantly affects the children’s perceived co-determination, and children with a migration history perceive significantly more co-determination than children without a migration history. The discussion concludes with implications emphasising the joint consideration of co-determination and teaching quality in practice.